2021
DOI: 10.1111/faf.12616
|View full text |Cite
|
Sign up to set email alerts
|

Finding the perfect mismatch: Evaluating misspecification of population structure within spatially explicit integrated population models

Abstract: Spatially heterogeneous environments influence almost every aspect of an organism's behaviour, ultimately influencing the resultant population dynamics and food-web interactions (Nathan et al., 2008). The impact of spatially dynamic landscapes results in complex population level responses including the formation of metapopulation structure, source-sink dynamics, predator-prey interactions, heterogeneous life history parameters and speciation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…Therefore, if movement is not occurring and other process variability is correctly specified, such as on natural mortality and selectivity, numbers at age can reasonably be excluded from the random effects. If substantial movement or stock mixing is occurring, models can account for this though auxiliary information like tagging data and/or restructuring management units to reflect closed populations (Berger et al, 2021;Bosley et al, 2022;Goethel et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, if movement is not occurring and other process variability is correctly specified, such as on natural mortality and selectivity, numbers at age can reasonably be excluded from the random effects. If substantial movement or stock mixing is occurring, models can account for this though auxiliary information like tagging data and/or restructuring management units to reflect closed populations (Berger et al, 2021;Bosley et al, 2022;Goethel et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…marlin can help researchers generate data for further testing of the performance and design of spatially explicit integrated population models, in the manner of Bosley et al. (2022). In addition, the process‐based movement model used in marlin can directly use empirical estimates of movement dynamics derived in the manner of Thorson et al.…”
Section: Discussionmentioning
confidence: 99%
“…We envision marlin being applicable to research on dynamic ocean management, range shifts, management strategy evaluation, policy interactions and spatial stock assessment. marlin can help researchers generate data for further testing of the performance and design of spatially explicit integrated population models, in the manner of Bosley et al (2022).…”
Section: Con Clus Ionsmentioning
confidence: 99%
“…With improved scientific understanding of the spatiotemporal nature of ecosystem drivers and the redistribution of marine species due to climate change, there has been an increase in the development of spatial assessment models to better represent spatial processes (Berger et al., 2017; Punt, 2019a, 2019b). Although spatially explicit simulation tools have demonstrated that spatial assessments are typically more robust than single‐region or spatially implicit (i.e., areas‐as‐fleets, AAF) approaches when spatial dynamics are present, there remains ambiguity as to the conditions that necessitate implementing a spatial assessment (Bosley et al., 2022; Guan et al., 2019; McGilliard et al., 2015; Punt et al., 2017). Moreover, operational application of spatial assessments tends to be focused on highly mobile, wide‐ranging large pelagic species (i.e., tunas; Punt, 2019a).…”
Section: Introductionmentioning
confidence: 99%